Differential Changes of Aorta and Carotid Vasodilation in Type 2 Diabetic GK and OLETF Rats: Paradoxical Roles of Hyperglycemia and Insulin. (1st October 2011) - Zhong, Mei-Fang; Shen, Wei-Li; Tabuchi, Masaki; Nakamura, Kyoko; Chen, Yi-Chen; Qiao, Cong-Zhen; He, Jin; Yang, Jie; Zhang, Chuan; Kamenov, Zdravko; Higashino, Hideaki; Chen, Hong
Abstract : We investigated large vessel function in lean Goto-Kakizaki diabetic rats (GK) and Otsuka Long-Evans Tokushima Fatty diabetic rats (OLETF) with possible roles of hyperglycemia/hyperosmolarity and insulin. Both young and old GK showed marked hyperglycemia with normal insulin level and well-preserved endothelium-dependent and endothelium-independent vasodilation in aorta and carotid artery. There were significant elevations in endothelial/inducible nitric oxide synthase (eNOS/iNOS) and inducible/constitutive heme oxygenase (HO-1/HO-2) in GK. The endothelium-dependent vasodilation in GK was inhibited partly by NOS blockade and completely by simultaneous blocking of HO and NOS. In contrast, OLETF showed hyperinsulinemia and mild hyperglycemia but significant endothelium dysfunction beginning at early ages with concomitantly reduced eNOS. Insulin injection corrected hyperglycemia in GK but induced endothelium dysfunction and intima hyperplasia. Hyperglycemia/hyperosmolarity in vitro enhanced vessel eNOS/HO. We suggest that hyperinsulinemia plays a role in endothelium dysfunction in obese diabetic OLETF, while hyperglycemia/hyperosmolarity-induced eNOS/HO upregulation participates in the adaptation of endothelium function in lean diabetic GK.